2003
DOI: 10.1038/sj.bjc.6600858
|View full text |Cite
|
Sign up to set email alerts
|

Role of RANKL-induced osteoclast formation and MMP-dependent matrix degradation in bone destruction by breast cancer metastasis

Abstract: Bone metastasis of breast cancer induces severe osteolysis with increased bone resorption. Osteoclast differentiation regulated by the receptor activator of NF-kB ligand (RANKL) in osteoblasts and matrix degradation induced by matrix metalloproteinases (MMPs) are thought to be involved in the process of bone resorption. When nude mice were inoculated with human breast cancer cells, MDA-MB-231(MDA-231), numerous osteoclasts resorbed bone and the degradation of the bone matrix markedly progressed in the femur an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 43 publications
3
77
1
Order By: Relevance
“…23,24,27 We demonstrate in our study that fixed BHY cells induced mainly TRAP þ mononuclear and binuclear cells but not MNCs. These results strongly suggest that living cell-to-cell contact among BHY cells and POBs is essential for osteoclast formation.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…23,24,27 We demonstrate in our study that fixed BHY cells induced mainly TRAP þ mononuclear and binuclear cells but not MNCs. These results strongly suggest that living cell-to-cell contact among BHY cells and POBs is essential for osteoclast formation.…”
Section: Discussionmentioning
confidence: 74%
“…29 On the other hand, not all cancers express RANKL and cell-to-cell contact between cancer cells and host cells does not always lead to RANKL expression. [26][27][28] Ohshiba et al 27 recently showed that MDA-231 cells, a breast cancer cell line, do not express RANKL. Nevertheless, addition of MDA-231 cells to cocultures of mouse BMCs and POBs induced osteoclast formation without osteotropic factors present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMPs have been detected in osteolytic bone lesions caused by tumors forming bone metastases, 33 and in vivo there is a marked expression of MMP-13 in bone metastases of mammary tumors. 34 In a mouse model, tumor-induced osteolysis was decreased by TIMPs. 35 This also suggests that osteolysis is closely connected with MMP activity, and that MMPs might be a therapeutic target to prevent osteolytic bone destruction.…”
Section: Discussionmentioning
confidence: 99%